T cell and monocyte requirements for erythropoiesis. - Linch, D; Boyle, D; Beverley, P (1982)
Progenitor cell fractions from normal human marrow have been prepared by a method that enables low numbers of cells to be cultured and results in very little T cell or monocyte contamination. The enrichment of 14- and 21-day BFU-E was similar to that for CFU-GM and the readdition of sheep red blood rosette-forming cells had no effect on BFU-E growth. The significance of the discrepancy in cellular requirements for the growth of blood and bone marrow BFU-E is discussed.